Studi Manajemen Kelembagaan Museum - Rohanda, -; Agustina, Susanti (Universitas Pendidikan Indonesia, 2015)
Abstrak. Museum menjadi aset bernilai sejarah yang monumental dan sarat dengan misi pendidikan dari generasi ke generasi. Museum pada umumnya menghadapi kendala dalam pengelolaan dana. Pengelolaan dana terutama yang mendukung keberlanjutan pemeliharaan, perbaikan, dan perawatan museum agar dapat melayani masyarakat lebih baik dan profesional. Kendala tersebut pada dasarnya akan selalu terkait dengan manajemen kelembagaan museum. Informasi yang diolah dalam karya ilmiah ini merupakan hasil elaborasi dari studi literatur dan simpulan studi hasil penelitian terdahulu. Artikel ilmiah ini membahas aspek kelembagaan museum meliputi pertama, profil museum dari segi sarana prasarana, SDM, koleksi; kedua aspek legal formal nomenklatur dan payung hukum; ketiga, aspek organisasi lembaga termasuk di dalamnya tugas, fungsi, wewenang, dan tanggung jawab lembaga penaung; keempat, pola koordinasi, kerjasama, dan hubungan kelembagaan museum dengan instansi terkait; kelima, studi kasusrevitalisasi kegiatan permuseuman yang mengarah pada kebijakan pengelolaankelembahgaan museum yang profesional. Pembahasaan tentang manajemen kelembagaan museum ini berguna, pertama bagi pengembangan wawasan keilmuan informasi dan perpustakaan, khususnya kelembagaan informasi selain perpustakaan. Kedua, memberikan gambaran mengenai tata kelola museum di instansi pemerintah. Ketiga, batasan lingkup kajian baru sebatas manajemen kelembagaan museum di instansi pemerintah, sehingga perlu adanyaÂ pengembangan kajian manajemen kelembagaan museum untuk tipe museumlainnya, seperti museum yang dikelola swasta maupun pribadi.Kata kunci: gawitra, kelembagaan informasi, manajemen, museum.Abstract. Museums are monumental historical assets and laden with educational mission from generation to generation. Museums in general face constraints in fund management especially to support the sustainability, repair, and maintenance of the museums in order to serve the public better and professionally. These constraints will basically always be associated with the museums' institutional management. The information processed in this paper is an elaboration of literature study and conclusions of previous studies. This scientific article discusses the institutional aspects of museums including first, the museums' profile in terms of infrastructure, human resources, collection; second, the formal legal aspects of nomenclature and legal protection; third, the institutions' organizational aspects including tasks, functions, authority, and responsibilities of the sheltering institutions; fourth, the pattern of coordination, cooperation and institutional relations museum with other relevant institutions; and fifth, case studies of revitalization of museum activities that lead to institutional management policies of professional museums.Discussion on of the institutional management of museums is useful, first, for thedevelopment of information and library science, particularly institution of information in addition to the library. Second, it provides an overview of the governance of the museum in government institutions. Third, the scope of study is limited to institutional management of museums in government institutions, thus there is a need for the development of studies on institutional management of museums for other types of museums, such as museums that are managed by private or personal institutions.Keywords: Gawitra, information institution, management, museum.